PENGARUH KEBIJAKAN FISKAL DAN MONETER TERHADAP STABILITAS MAKROEKONOMI DI INDONESIA - Gulo, Raya Rich Fanotona; Efendi, Bakhtiar (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This research aims to determine the influence between fiscal mix policy and monetary policy in order to maintain macroeconomic stability as seen by monetary and fiscal indicators on macroeconomics. The method used is Vector Autoregression by completing assumption tests and estimates on the research variables tax, government spending, exchange rates, interest rates, money supply and gross domestic product. The time series research data for 2008-2022 is sourced from the World Bank with the results obtained that government spending is influenced by the amount of money in circulation and tax revenues, interest rates influence tax results, the amount of money flowing also influences exchange rate figures and gross domestic product has an influence. by exchange rates and taxes. Shows that monetary policy and fiscal policy have a mutually influential relationship on macroeconomic stability in Indonesia. With these two policies, they become a policy mix that can describe the economy in Indonesia, so that the use and implementation of fiscal and monetary policies must always be controlled efficiently.